The Effect of Immersion Doses of Hybrid Coconut Water on Guppy (Poecillia reticulata) to Increase the Male Larvae Percentage - Dio Gilang Sulistyo; Titik Susilowati; Seto Windarto (Sains Akuakultur Tropis : Indonesian Journal of Tropical Aquaculture, 2021)
Abstract Guppy fish is one type of ornamental fish that has its charm where it has beautiful colours and a slender body shape. Male guppy fish are more attractive, have more beautiful colour patterns, longer tail fins, and a slimmer body than female guppies. Hence, their selling price is much higher and is in demand in the market in the ornamental fish industry. One way that can be done to produce male guppy fish is by using the sex reversal or masculinization method. The sex reversal method that can be used is to use a solution of young hybrid coconut water (Cocos nucifera) with different doses. The immersion process will affect the percentage of male sex in guppy fish because in the young coconut water solution there is a content of potassium which plays a role in the sex reversal process which functions to regulate testosterone regulation in the body and direct the work of androgens. The purpose of this study was to determine the effect of young coconut water on the sex ratio of male guppies resulting from the immersion of female broodfish and to determine the best dose for the success rate of masculinization of guppy fish. The research was conducted from April to June 2020 in guppy fish farmers in Sidomulyo Village, East Ungaran District, Semarang Regency. The test animal used was the Black Moscow fish. This study used an experimental method with a completely randomized design of 4 treatments and 3 replications. Treatment of different immersion doses of young coconut water solution used were A (without immersion), B (40%), C (45%), D (50%). The data observed included the percentage of the male sex, survival rate and water quality. The results obtained from the research showed that the percentage value of male guppy fish was treated A (50.57 ± 3.48%), B (84.90 ± 2.55%), C (90.42 ± 1.67%), D (96.90 ± 1.34%). The results of the survival rate are treatment A (98.91 ± 0.95%), B (95.58 ± 2.48%), C (91.25 ± 3.46%), D 84.36 ± 3.62 %. The results of water quality observations were in the form of temperatures ranging from 26.9-28.9 ℃, pH (7.2-7.9), and DO ranging from 3.5-5.5 mg/ L. The conclusion was that immersion of young coconut water solution in pregnant guppy broods with different doses had a significant effect (P <0.05) on the percentage of the male sex. The best treatment was treatment D (50%) which resulted in the percentage value of male sex 96.90 ± 1.34%. Keywords: Black Moscow, potassium, masculinization, androgen hormone